Impact of habituated dietary protein intake on fasting and postprandial whole-body protein turnover and splanchnic amino acid metabolism in elderly men: a randomized, controlled, crossover trial. Issue 6 (25th July 2020) - Højfeldt, Grith; Bülow, Jacob; Agergaard, Jakob; Asmar, Ali; Schjerling, Peter; Simonsen, Lene; Bülow, Jens; van Hall, Gerrit; Holm, Lars
ABSTRACT: Background: Efficacy of protein absorption and subsequent amino acid utilization may be reduced in the elderly. Higher protein intakes have been suggested to counteract this. Objectives: We aimed to elucidate how habituated amounts of protein intake affect the fasted state of, and the stimulatory effect of a protein-rich meal on, protein absorption, whole-body protein turnover, and splanchnic amino acid metabolism. Methods: Twelve men (65–70 y) were included in a double-blinded crossover intervention study, consisting of a 20-d habituation period to a protein intake at the RDA or a high amount [1.1 g · kg lean body mass (LBM) −1 · d −1 or >2.1 g · kg LBM −1 · d −1, respectively], each followed by an experimental trial with a primed, constant infusion of D8 -phenylalanine and D2 -tyrosine. Arterial and hepatic venous blood samples were obtained after an overnight fast and repeatedly 4 h after a standardized meal including intrinsically labeled whey protein concentrate and calcium-caseinate proteins. Blood was analyzed for amino acid concentrations and phenylalanine and tyrosine tracer enrichments from which whole-body and splanchnic amino acid and protein kinetics were calculated. Results: High (compared with the recommended amount of) protein intake resulted in a higher fasting whole-body protein turnover with a resultant mean ± SEM 0.03 ± 0.01 μmol · kg LBM −1 · min −1 lower net balance ( P < 0.05), which was not rescued by the intake of a protein-dense meal. The mean ± SEM plasma protein fractional synthesis rate was 0.13 ± 0.06%/h lower ( P < 0.05) after habituation to high protein. Furthermore, higher fasting and postprandial amino acid removal were observed after habituation to high protein, yielding higher urea excretion and increased phenylalanine oxidation rates ( P < 0.01). Conclusions: Three weeks of habituation to high protein intake (>2.1 g protein · kg LBM −1 · d −1 ) led to a significantly higher net protein loss in the fasted state. This was not compensated for in the 4-h postprandial period after intake of a meal high in protein. This trial was registered at clinicaltrials.gov as NCT02587156.